Aesthetic Interpretation of the Qur'an Sarah R. Bin Tyeer: A Critical Study - Manshur, Fadlil Munawwar (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
This study discusses Sarah R. Bin Tyeer’s views concerning Al-Qur’an aesthetics. This article emphasizes that people who read pre-modern Arabic-Islamic literature often encounter themes of binary opposition within them, for example, the conflict between the sacred and the profane, the pious and the godless. In the Arab-Islamic tradition, literary and aesthetic elements are pre-modern, modern, and contemporary literary expressions that show the continuity of the influence of Al-Qur’an as a sacred entity. Tyeer thinks that there have been many scientific studies placing Al-Qur’an in the history of literature and investigating its influence on Arabic literature. Through critical discourse analysis method, this study has tried to describe, interpret, and critically explain Al-Qur’an esthetics discourse. This method has proven that Tyeer’s ideas concerning Al-Qur’an aesthetics are considered appropriate in elaborating and exploring the relationship between Tyeer’s thoughts on Al-Qur’an aesthetics with the cultural and social contexts that surround it. Tyeer also succeeded in explaining the relationship between the use of the beauty of Al-Qur’an language and Arab social and cultural practices. In this case, Tyeer’s view is focused on the text and context, not on the scientific paradigm.